PEEK Implants: An Innovative Solution for Facial Aesthetic Surgery - Rocco Narciso; Emanuela Basile; Davide Johan Bottini; Valerio Cervelli (Case Reports in Surgery)
The authors present a case report showing their experience with the use of PolyEtherEtherKetone (PEEK) implants as an innovative solution for the skeleton and soft tissues’ reshaping in facial aesthetic plastic surgery. This technique offers the surgeon a reliable and effective way to answer patients’ request of increasing volume and reshaping the malar area. A fifty-year-old patient complaining about hypoplasia of the malar area, after undergoing three operations of silicon implants’ placement and replacement, was still unsatisfied about the symmetry and feeling through the skin of the lower lid, the rim of the prostheses. The authors suggested the use of bone-anchored PEEK implants, to increase the volume and reshape the malar area by a skeleton and soft tissue camouflage. The treatment was planned and previewed on the preop 3-dimensional CT scans for the customization of the implants. Although no cases are reported in international literature on the use of this material in facial aesthetic surgery, this technique seems to offer a safe and effective solution for the treatment of patients asking to increase and modify the shape of their malar area. Custom made PEEK implants are already used in craniofacial reconstructive bony surgery with good results, and 3D CT scan planning is widely used in these cases. No complications were reported in the case reported and the outcomes seem to the authors and to the patient being, finally, satisfactory.